PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MATERI PENGUKURAN BERBASIS SAINTIFIK PADA ANAK KELOMPOK B DI TAMAN KANAK-KANAK - Widiya Astuti; Syafdaningsih syafar; sri sumarni (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This study aims to produce worksheets for students of scientific-based measurement material in group B children in kindergartens that are valid and practically tested. This type of research is the development using the Rowntree model, namely the planning, development, evaluation stages. Evaluation using Tessmer's formative evaluation methods includes self evaluation, expert review, one to one evaluation, and small group evaluation. Analysis of data from expert reviews obtained an average of 87% with valid categories including validation of content, constructs and media. This means that the LKPD is in accordance with the contents of the measurement material for group B children, then the construct includes the readability and suitability of the image, while the media is seen from the packaging of the student worksheet (LKPD), display design, use of fonts and font sizes and illustrations of student worksheets (LKPD). In the one to one evaluation and small group evaluation and product stages the average percentage was 94% with a very practical category. To achieve a valid and practical LKPD perfection there is still a recognized lack of validity of 13% and to achieve practicality still have a deficiency of 6%